SPEECH FUNCTION OF ENGLISH CLASSROOM INTERACTION AT 12TH GRADE OF SMK TEKNOLOGI NASIONAL BEKASI - Pradita Cahya Ananda; Ika Chairiyani (Jurnal Web Informatika Teknologi, 2022)
The goal of this study was to discover and describe classroom interaction in the English teaching and learning process at SMK Teknologi Nasional Bekasi's eighth grade. This study was conducted in the form of a descriptive qualitative study with a naturalistic approach. Observations through online systems and in-depth interviews were used to collect data for this study at SMK Teknologi Nasional Bekasi. The result was (1) interaction in pre-teaching, which was further divided into four categories: greeting, asking students' conditions, checking students' attendance, and announcing the materials that would be learned by the students in the meeting; (2) interaction in while-teaching, which was further divided into three categories: motivating students to learn, rewarding students, and assisting students in learning the material; and (3) interaction in post-teaching.